Using the MINT Database to Search Protein Interactions. Issue 1 (16th January 2020) - Calderone, Alberto; Iannuccelli, Marta; Peluso, Daniele; Licata, Luana
Abstract: The Molecular INTeractions Database (MINT) is a public database designed to store information about protein interactions. Protein interactions are extracted from scientific literature and annotated in the database by expert curators. Currently (October 2019), MINT contains information on more than 26, 000 proteins and more than 131, 600 interactions in over 30 model organisms. This article provides protocols for searching MINT over the Internet, using the new MINT Web Page. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Searching MINT over the internet Alternate Protocol : MINT visualizer Basic Protocol 2 : Submitting interaction data